Risk Factors of Catheter-Associated Urinary Tract Infections in Hospitalized Patients in Internal Medicine Ward of Tertiary Referral Hospital in Indonesia - Hana; Asmarawati, Tri Pudy; Juniastuti (Jurnal Medis Islam Internasional, 2025)
Introduction: Urinary Tract Infection (UTI) is the most common type of nosocomial infection. An increase of 80% of nosocomial urinary tract infections is caused by the usage of urinary catheters. Previous studies have found that inpatients are more susceptible to UTI than outpatients. Objective: The Objective of this study is to assess the prevalence and risk factors for internal medicine patients at tertiary referral hospitals in Surabaya with Catheter Associated Urinary Tract Infections (CAUTI). These findings may aid in strategies to minimize CAUTI occurrences. Methods: This study was a single-center cross-sectional study that obtained data from medical records. Data samples were tested using Chi-Square to find a correlation between UTI and age, gender, length of stay, and underlying disease or comorbidities with a p-value of p<0,05. Results: The proportion of patients who experienced CAUTI during May 2020-May 2021 was 32.8%. The characteristics of the sample in this study were in the age range of 28 to 78 years with an average of 54 years. There were four male patients and 17 female patients in the CAUTI group. The p-values for age, gender, duration of hospitalization, and underlying disease or comorbidities were 0.465 (p>0.05); 0.064 (p>0.05); 0.146 (p>0.05); and 0.064 (p>0.05). Conclusions: There was a reduction in the prevalence of CAUTI from 2018 compared to 2020-2021. There were no variables that were significantly associated as risk factors for CAUTI.